2014
DOI: 10.1515/bejeap-2013-0180
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility Policies and Re-employment Probabilities in Italy

Abstract: We analyze the effects of Italian labor market reforms "at the margin" on the probability of exiting from non-employment and entering permanent and temporary contracts, using WHIP data for the period 1985-2004. We find that the reforms have strengthened the duration dependence parameter, meaning a stronger labor market gap in employment opportunities between the short-and long-term non-employed. We suggest that in a flexible labor market, long-term unemployment is used by firms as a screening device to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…The crucial issue of the effective length of unemployment/non-employment spells is seldom documented. Mroz and Savage (2006) report re-employment probabilities for youth in the U.S. who experienced unemployment spells of 10 years or more; evidence of the same order of magnitude is provided by Gomes (2012) in his study of the U.K.; Mussida and Sciulli (2015) explore the Italian case and provide estimates of re-employment probabilities after layoff which are consistent with our findings.…”
Section: R E V I S E D P R O O Fsupporting
confidence: 81%
“…The crucial issue of the effective length of unemployment/non-employment spells is seldom documented. Mroz and Savage (2006) report re-employment probabilities for youth in the U.S. who experienced unemployment spells of 10 years or more; evidence of the same order of magnitude is provided by Gomes (2012) in his study of the U.K.; Mussida and Sciulli (2015) explore the Italian case and provide estimates of re-employment probabilities after layoff which are consistent with our findings.…”
Section: R E V I S E D P R O O Fsupporting
confidence: 81%
“…Evidence of the same order of magnitude is provided by P. Gomes (2012) in his study on the UK. Mussida and Sciulli (2015) explore the Italian case and provide estimates of re-employment probabilities after layoff which are consistent with our findings.…”
Section: A Short Overview Of Literaturesupporting
confidence: 79%
“…Some years before Abbring et al (2005) had indicated that state dependence persists also when selection issues related to workers' heterogeneity are included in the analysis. Mussida and Sciulli (2015) explore the effect of labour market flexibilisation policy for the Italian case and provide evidence that re-employment probabilities decreased after those reforms. According to Machin and Manning (1999), however, state dependence and workers' heterogeneity cannot be identified separately without untenable assumptions.…”
Section: A Short Survey Of Relevant Literaturementioning
confidence: 99%